Menopause care in women living with HIV in the UK - A review - B. Dragovic; J. Rymer; N. Nwokolo (Elsevier, 2022)
Advances in HIV care over the last 30 years have transformed a virtually fatal condition into a chronic, manageable one. Antiretroviral therapy (ART) has dramatically changed the outlook for people living with HIV so that most individuals with well controlled disease have a normal life expectancy. As result of this increase in life expectancy, one-third of women living with HIV are of menopausal age.Adding to the shift in age distribution, rates of new HIV diagnosis are increasing in the over 50-year age group, likely the result of a combination of low condom use and perception of transmission risk and in women, an increased risk of HIV acquisition due to the mucosal disruption that accompanies vaginal atrophy.Many women living with HIV are unprepared for menopause, have a high prevalence of somatic, urogenital and psychological symptomatology and low rates of menopausal hormone therapy (MHT) use. Many women experience enormous frustration shuttling between their general practitioner and HIV care provider trying to have their needs met, as few HIV physicians have training in menopause medicine and primary care physicians are wary of managing women living with HIV, in part, because of fears about potential drug-drug interactions (DDIs) between MHT and ART.Several data gaps exist with regard to the relationship between HIV and the menopause, including whether the risk of HIV transmission is increased in virally-suppressed women with vaginal atrophy, whether or not menopause amplifies the effects of HIV on cardiovascular, psychological and bone health, as well as the safety and efficacy of MHT in women living with HIV.Menopausal women living with HIV deserve high quality individualised menopause care that is tailored to their needs. More research is needed in the field of HIV and menopause, primarily on cardiovascular disease and bone health outcomes as well as symptom control, and strategies to reduce HIV acquisition, encourage testing, and maintain older women in care in order to inform optimal clinical management.